Walking down the street. (Journal of Parents and Teachers, 2025)
The article reflects on experiences that happen on the street and the fact that people are becoming less tolerant and more demanding. It also lists a series of circumstances that occur in public spaces and how they are resolved.
Keywords: streets; circumstances; tolerance; demands